2019
DOI: 10.1021/acsbiomaterials.8b01176
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasmall Au–Ag Alloy Nanoparticles: Protein-Directed Synthesis, Biocompatibility, and X-ray Computed Tomography Imaging

Abstract: The ultrasmall sizes of nanoparticles have attracted significant attention for potential applications in the fields of catalysis and nanomedicine. Herein, we reported on the green preparation and X-ray computed tomography (CT) imaging of ultrasmall bimetallic bovine serum albumin-directed gold–silver (Au–Ag@BSA) nanoparticles (2–4 nm) using BSA as a stabilizing and template-directed agent. Further, the effects of synthesis conditions were systematically explored to prepare products by adjusting the different m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…It has been reported that stable GO-coated Fe3O4 nanocomposites are successfully used as a robust drug delivery carrier for simultaneous tumor MR imaging and targeted therapy [5]. Moreover, the innovative contrast agents for tumor imaging such as ultrasmall bimetallic bovine serum albumin-directed gold-silver (Au-Ag@BSA) nanoparticles have attracted significant attention for potential applications in the fields of multifunctional nanomedicine [6].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that stable GO-coated Fe3O4 nanocomposites are successfully used as a robust drug delivery carrier for simultaneous tumor MR imaging and targeted therapy [5]. Moreover, the innovative contrast agents for tumor imaging such as ultrasmall bimetallic bovine serum albumin-directed gold-silver (Au-Ag@BSA) nanoparticles have attracted significant attention for potential applications in the fields of multifunctional nanomedicine [6].…”
Section: Introductionmentioning
confidence: 99%
“…Although CT imaging is often used in combination with PET, it can act as an independent imaging modality [ 183 ]. Chu et al [ 184 ] used BSA as a biotemplate to make ultrasmall Au–Ag@BSA bimetallic protein nanoparticles with an average size of 2–4 nm. They manipulated the ratio of gold to silver in the synthesis of nanoparticles.…”
Section: Protein Nanoparticles As Contrast Agents’ Carriers For Cancer Imagingmentioning
confidence: 99%
“…(2013) designed a silica-coated FA-modified AuNCs targeting FR (+) MGC803 and FR (−) GES-1 cells for dual-mode imaging of FL and CT in gastric cancer ( Figure 8 B). Chu et al. (2019) in BSA-AuNCs introduced Ag + and found that a molar ratio of Au: Ag of 3:2 showcased the best X-ray attenuation coefficient, approximately twice that of iohexol (80 mM concentration).…”
Section: Advances Of Auncs Applied In Bioimagingmentioning
confidence: 99%